Multiple wave solutions and auto-Bäcklund transformation for the (3+1)-dimensional generalized B-type Kadomtsev–Petviashvili equation - Cheng, Li; Zhang, Yi (Computers & mathematics with applications (1987), 2015)
The multiple Exp-function method is used to construct multiple wave solutions to the (3+1)-dimensional generalized BKP equation. The resulting solutions involve generic phase shifts and wave frequencies containing some existing choices. By taking the standard truncated Painlevé analysis, we obtained an auto-Bäcklund transformation and some types of exact solutions of the (3+1)-dimensional generalized BKP equation. Moreover, the linear superposition principles of hyperbolic and trigonometric function solutions are also presented.